In situ growth of covalent organic framework on titanium fiber for headspace solid-phase microextraction of 11 phthalate esters in vegetables. (15th July 2020) - Yue, Qi; Huang, Yu-Ying; Shen, Xiao-Fang; Yang, Cheng; Pang, Yue-Hong
Highlights: Covalent organic framework TpBD grows on titanium wire via TiO2 nanotube arrays. TpBD-TiO2 fiber has good thermal stability and long lifetime. HS-SPME on the fiber exhibits excellent extraction efficiency for trace PAEs. Coupled with GC-MS/MS, it presents a sensitive methodology for PAEs determination. Abstract: Vegetables are easily contaminated by phthalate esters (PAEs) from the environment, agricultural films and fertilizers, affecting human health. In this paper, titanium dioxide (TiO2 ) nanotube arrays were prepared by electrochemical anodic oxidation on the surface of titanium wire. Covalent organic framework of TpBD was in situ bonded to the titanium wire via TiO2 nanotube arrays using monomers of 1, 3, 5-trimethylphloroglucinol (Tp) and benzidine (BD). The fabricated TpBD-TiO2 coated titanium wire was used as the solid-phase microextraction fiber to extract 11 PAEs in vegetable samples. Coupled with gas chromatography-tandem mass spectrometry (GC–MS/MS), the limits of detection for PAEs were from 0.001 (di- n -butyl phthalate) to 0.430 (butyl benzyl phthalate) μ g/L (S/N = 3) and enrichment factors were between 226 (dimethyl phthalate) and 2154 (di- n -butyl phthalate). Our fabricated TpBD-TiO2 fiber can be used at least 150 times without significant loss of extraction efficiency (<4.8%). Quantitative determination of PAEs in vegetable samples (tomato, lettuce, cucumber) was achieved by standard addition.